Analisis Pembelajaran Materi IPS Kurikulum Merdeka Di Sekolah Dasar Negeri 1 Bungi - Arjunita Rambe; Ninik Indawati; Cicilia Ika Rahayu Nita (Jurnal Penelitian dan Pendidikan IPS, 2026)
This study aims to describe the planning, implementation, and evaluation of learning the topic “social interaction in daily life” by teachers at Sekolah Dasar Negeri 1 Bungi in the 2025/2026 academic year. A qualitative approach was employed to examine the challenges faced by teachers in implementing the Merdeka Curriculum in social studies learning. The research subjects included the social studies teacher, the vice principal as managerial support, and fifth-grade students actively participating in the learning process. The findings indicate that lesson planning focused on student-centered learning with contextual themes, learning objectives based on Learning Outcomes, and differentiation through project-based learning. The implementation was interactive and contextual, using projects, group discussions, and problem-based learning, while utilizing local learning resources. Evaluation applied a holistic assessment combining formative, summative, and authentic approaches through portfolios, projects, reflections, and observations, supported by constructive feedback to enhance students’ competencies in accordance with the Merdeka Curriculum principles.